Students’ spontaneous smile in efl classroom - Nóbrega, Daniela Gomes de Araújo (Signótica, 2012)
This article discusses the importance of the students’ spontaneous smile in EFL classroom interaction, and its implication to their oral production. Findings proved that the students’ spontaneous smile served as a fundamental interactive nonverbal sign for it not only favors a closer relation among students, but also helps them in the co-construction of oral activities in group works. In sum, the students’ spontaneous smile appeared to be a nonverbal indicative of proximity and of increasing oral interaction among them.